Enhancing epi-cedrol production in escherichia coli by fusion expression of farnesyl pyrophosphate synthase and epi-cedrol synthase - Navale, Govinda R; Sharma, Poojadevi; Said, Madhukar S; Ramkumar, Sudha; Dharne, Mahesh S; Thulasiram, H., V; Shinde, Sandip S (Engineering in Life Science, 2019)
Terpene synthase catalyses acyclic diphosphate farnesyl diphosphate into desired sesquiterpenes. In this study, a fusion enzyme was constructed by linking Santalum album farnesyl pyrophosphate synthase (SaFPPS) individually with terpene synthase and Artemisia annua Epi-cedrol synthase (AaECS). The stop codon at the N-terminus of SaFPPS was removed and replaced by a short peptide (GSGGS) to introduce a linker between the two open reading frames. This fusion clone was expressed in Escherichia coli Rosseta DE3 cells. The fusion enzyme FPPS-ECS produced sesquiterpene 8-epi-cedrol from substrates isopentenyl pyrophosphate and dimethylallyl pyrophosphate through sequential reactions. The K-m values for FPPS-ECS for isopentyl diphosphate was 4.71 mu M. The fusion enzyme carried out the efficient conversion of IPP to epi-cedrol, in comparison to single enzymes SaFPPS and AaECS when combined together in enzyme assay over time. Further, the recombinant E. coli BL21 strain harbouring fusion plasmid successfully produced epi-cedrol in fermentation medium. The strain having fusion plasmid (pET32a-FPPS-ECS) produced 1.084 +/- 0.09 mg/L epi-cedrol, while the strain harbouring mixed plasmid (pRSETB-FPPS and pET28a-ECS) showed 1.002 +/- 0.07 mg/L titre in fermentation medium by overexpression and MEP pathway utilization. Structural analysis was done by I-TASSER server and docking was done by AutoDock Vina software, which suggested that secondary structure of the N- C terminal domain and their relative positions to functional domains of the fusion enzyme was greatly significant to the catalytic properties of the fusion enzymatic complex than individual enzymes.

Improvement in serum amylase and glucose levels in diabetic rats on oral administration of bisdemethoxycurcumin from Curcuma longa and limonoids from Azadirachta indica - Ramkumar, Sudha; Thulasiram, V. H.; RaviKumar, Ameeta (Journal of Food Biochemistry, 2021)
Curcuma longa and Azadirachta indica are traditionally used in Indian cuisine and Ayurvedic medicine as nutraceuticals against diabetes. The crude C. longa isopropanol extract, bisdemethoxycurcumin (BDMC), the purified bioactive component from C. longa, and limonoids azadiradione, gedunin from A. indica, are able to inhibit in vitro the antidiabetic target human pancreatic alpha-amylase independently. However, no reports on their in vivo efficacy in animal models exist. Thus, the antidiabetic effect of these orally administered human pancreatic alpha-amylase inhibitors was performed on streptozotocin-induced Sprague-Dawley rats. Initially, the normal rats were treated with test compounds (10-100 mg/kg of body weight) in corn oil (5 ml/kg), and as no lethality was observed in these doses, further studies were carried out with lowest concentration of 10 mg/kg of body weight. A reduction in area under curve (AUC) suggested glucose-lowering effect of these compounds in starch fed diabetic rats. The efficacy study showed a significant improvement in body weight, blood glucose levels, serum amylase, and fructosamine levels as well in other serum parameters associated with diabetes with respect to liver and renal functions. Hence, under in vivo conditions, inhibition of alpha-amylase activity by BDMC and limonoids affirms it as one of the mechanisms of action resulting in reduction of blood glucose levels. Practical applications Bisdemethoxycurcumin from C. longa and limonoids, namely, azadiradione and gedunin, from A. indica are potent inhibitors of the antidiabetic target human pancreatic alpha-amylase. Oral Starch Tolerance Test (OSTT) and 28-day efficacy study to check the effect of these orally administered inhibitors in diabetic rat models showed significant improvements in serum blood glucose and amylase levels as well as in other diabetes related serum parameters, namely, bilirubin, lipids, lactate dehydrogenase, alkaline phosphatase, and urea. The study contributes to understanding the action and efficacy of these pancreatic alpha-amylase inhibitors and suggests a potential role for them as nutraceuticals/therapeutics in management of post-prandial hyperglycemia.
Keywords: ‐ α Amylase inhibitors; Azadiractha indica; BDMC; Curcuma longa; in vivo rat studies; Limonoids

On the use of electronegativity and electron affinity based pseudo-molecular field descriptors in developing correlations for quantitative structure-activity relationship modeling of drug activities - Kunde, Pushkar D.; Ramkumar, Sudha; Kamble, Sanjay P.; RaviKumar, Ameeta; Kulkarni, Bhaskar D.; Kumar, V. Ravi (Chemical Biology & Drug Design, 2021)
For quantitative structure-activity relationship (QSAR) modeling in ligand-based drug discovery programs, pseudo-molecular field (PMF) descriptors using intrinsic atomic properties, namely, electronegativity and electron affinity are studied. In combination with partial least squares analysis and Procrustes transformation, these PMF descriptors were employed successfully to develop correlations that predict the activities of target protein inhibitors involved in various diseases (cancer, neurodegenerative disorders, HIV, and malaria). The results show that the present QSAR approach is competitive to existing QSAR models. In order to demonstrate the use of this algorithm, we present results of screening naturally occurring molecules with unknown bioactivities. The pIC(50) predictions can screen molecules that have desirable activity before assessment by docking studies.
Keywords: drug discovery; electron affinity; Electronegativity; molecular field descriptors; partial least squares; QSAR

Targeted metabolite profiling and de novo transcriptome sequencing reveal the key terpene synthase genes in medicinally important plant, Couroupita guianensis Aubl - Thulasiram, Hirekodathakallu V.; Karegaonkar, Shrikant Jagannathrao; Sharma, Poojadevi; Kumar, Ashish; Ramkumar, Sudha; Pandreka, Avinash (Plant Genetic Resources-Characterization and Utilization, 2023)
The Lecythidaceae family tree, Couroupita guianensis Aubl, popularly known as Nagpushpa, is a widely cultivated ornamental tree with several uses in traditional medicine. The tree is revered as highly sacred in Indian traditional culture due to its uniquely shaped, fragrant flowers. Considering the significance, we were prompted to carry out the metabolite and transcriptome analysis of Nagapushpa. The flower, petals, stamen, stem and leaf of C. guianensis were metabolically profiled, and it was discovered that the flower tissue contained the highest terpenoid reservoir. A number of terpenoid pathway transcripts were also found in the flower tissue after transcriptome profiling. KEGG pathway mapping was carried out to correlate transcript sequences with the biosynthesis of different types of terpenes. We were able to clone three full-length terpene synthase gene candidates, i.e. monoterpene ocimene synthase, diterpene ent-kaurene synthase and sesquiterpene farnesene synthase. The transcript expression of selected terpene synthase genes was also verified in flower tissue. These cloned sequences were used for in silico structural investigations and protein function prediction at the level of 3D structure. The data presented in this study provide a comprehensive resource for the metabolic and transcriptomic profiles of C. guianensis. The study paves the way towards the elucidation of terpene biosynthetic pathway in C. guianensis and heterologous production of useful terpenoids in the future.
Keywords: Couroupita guianensis Aubl; flower; Metabolite profiling; terpene synthases; Transcriptomics